The Role of Early Detection of Growth and Development in Identifying the Impact of Malnutrition and Stunting in Early Childhood - Nasution, Homsani; Widia, Arneta; Ritonga, Ade Nurcahyani; Siregar, Zuhrona; Fitri, Raya Idul; Safitri, Inayatu (Lembaga Riset Mutiara Akbar, 2025)
Stunting and malnutrition in early childhood remain serious global health issues, particularly in Indonesia. According to the 2022 Indonesian Nutritional Status Survey (SSGI), the national stunting prevalence reached 21.6%, a decrease from the previous year, but still above the WHO threshold of 20%. This situation reflects a gap between nutritional intervention theory and the reality of implementation in the field, particularly in the aspect of early detection of growth and development. This study used a literature review method by reviewing various relevant national and international research results from 2019–2024. The results indicate that the implementation of the Early Growth and Development Stimulation, Detection, and Intervention (SDIDTK) program plays a crucial role in identifying growth and development disorders due to malnutrition and stunting in early childhood. Integrated implementation of SDIDTK with health and education services has been shown to increase the effectiveness of interventions and accelerate the reduction of stunting rates. In conclusion, strengthening the early detection system for growth and development through cross-sectoral synergy is a fundamental strategy for creating a healthy and high-quality generation of Indonesian children.